Non-alcoholic fatty liver disease in metabolic syndrome patients in Serdang Hospital: quantification by contrast-enhanced computed tomography - Suppiah, Subapriya; Lee, Roy-Ming Chow; Sazali, Nor Sharmin; Abu Hassan, Hasyma (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Introduction: Non-alcoholic Fatty Liver Disease (NAFLD) is one of the end organ damage detected in patients having metabolic syndrome X and it can lead to chronic liver failure. Therefore, it is important to be able to assess the condition in a quantifiable manner to help clinicians recognize and treat this disease. Objective: We aimed to determine the prevalence of NAFLD in patients with metabolic syndrome in Serdang Hospital, Malaysia using contrast-enhanced multidetector computed tomography (CECT) abdominal scan. The study also aimed to calculate the quantification of NAFLD using liver to spleen density CT Hounsfield Unit ratio, CTL/S or CTL/S measurement using abdominal CECT scans. Furthermore, we aimed to verify the correlation of dyslipidemia with NAFLD based on the CTL/S parameter. Materials and Method: We conducted a cross-sectional retrospective study in Hospital Serdang, Malaysia using data from January 2012 to December 2013. The sample size was 279 patients with metabolic syndrome who had undergone CECT abdominal scan. Patient demographics were descriptively analysed. Spearman’s correlation test was used to look for association among lipid profile, blood sugar level and CTL/S ratio. Results: The prevalence of NAFLD in metabolic syndrome patients in our population was 82.8%. Prevalence of NAFLD was high among the elderly population (≥ 57 years old). Additionally, Indian ethnics with metabolic syndrome had the highest risk of developing NAFLD (90.9%). There was a significant association between elevated LDL levels and CTL/S ratio (p<0.05); indicative of severity of NAFLD in metabolic syndrome patients. Conclusion: Contrast-enhanced CT scan can help to non-invasively detect and quantify the severity of non-alcoholic fatty liver disease using the CTL/S ratio in patients with metabolic syndrome who are referred for the scan for certain clinical indications. However, we do not recommend it as a stand-alone, first line investigation in the management of NAFLD in metabolic syndrome patients.